The Use of Microneedles as an Alternative to Injections and Oral Medications for HIV Patients - Al-Farisi, Muhammad Salman; Pujiati, Ayu (Jurnal Berkala Kesehatan, 2025)
HIV/AIDS is a chronic disease that requires lifelong antiretroviral (ARV) therapy. However, conventional delivery methods such as oral and injectable medications, often present challenges including pain, poor adherence, and limited access to healthcare services, particularly in remote areas. This study aimed to systematically review the effectiveness of microneedle technology as an alternative ARV drug delivery method. A comprehensive literature search was conducted using PubMed, Scopus, ScienceDirect, SpringerLink, and Google Scholar databases. Studies were selected based on inclusion criteria following the PICOS framework, and data synthesis was performed in accordance with the PRISMA guidelines. The study demonstrated that microneedles (particularly the soluble and hydrogel varieties) are capable of effectively delivering ARVs through the skin, with promising pharmacokinetic responses. This technology is minimally invasive, painless, and easier to self-administer, potentially improving adherence in HIV patients. Microneedle- based drug delivery technology is promising as an alternative to ARV therapy. Further research is needed to test long-term effectiveness and patient acceptability on a broader clinical scale.